2008
DOI: 10.1128/jb.00206-08
|View full text |Cite
|
Sign up to set email alerts
|

Differential Transcriptional Analysis of the Cyanobacterium Cyanothece sp. Strain ATCC 51142 during Light-Dark and Continuous-Light Growth

Abstract: We analyzed the metabolic rhythms and differential gene expression in the unicellular, diazotrophic cyanobacterium Cyanothece sp. strain ATCC 51142 under N 2 -fixing conditions after a shift from normal 12-h light-12-h dark cycles to continuous light. We found that the mRNA levels of ϳ10% of the genes in the genome demonstrated circadian behavior during growth in free-running (continuous light) conditions. The genes for N 2 fixation displayed a strong circadian behavior, whereas photosynthesis and respiration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
161
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(175 citation statements)
references
References 57 publications
10
161
0
1
Order By: Relevance
“…Crocosphaera diel gene expression T Shi et al expression profile and found to be under circadian control (Toepel et al, 2008). However, genes for DNA replication were not among the cycling genes in Cyanothece (Stöckel et al, 2008).…”
Section: Crocosphaera Diel Gene Expression T Shi Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Crocosphaera diel gene expression T Shi et al expression profile and found to be under circadian control (Toepel et al, 2008). However, genes for DNA replication were not among the cycling genes in Cyanothece (Stöckel et al, 2008).…”
Section: Crocosphaera Diel Gene Expression T Shi Et Almentioning
confidence: 99%
“…The expression of nitrogenase genes in Trichodesmium and in the intertidal or coastal marine unicellular cyanobacterium Cyanothece sp. strain 51142 has been shown to be under circadian control (Schneegurt et al, 1994;Chen et al, 1998;BermanFrank et al, 2001;Toepel et al, 2008). Genome-wide diel expression analysis may further elucidate the mechanism mediating the spatial/temporal segregation of oxygenic photosynthesis and N 2 fixation in diazotrophic cyanobacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nifB gene, which forms part of the nifBQ cluster and is necessary for the processing of the Fe-Mo cofactor encoded by nifHDK (Roberts et al, 1978), was also highly represented among the daytime transcripts, in line with expression observed in Cyanothece sp. ATCC 51142 (Toepel et al, 2008). Finally, a hypothetical protein flanked by nifZ and nifP (Cwat_DRAFT_3843) had the greatest number of transcripts; however, its function in nitrogenase is unknown and it may be an attractive target for expression studies.…”
Section: Resultsmentioning
confidence: 99%
“…In Cyanothece sp. ATCC 51142, differential expression of nitrogenase cluster genes occurs over diel cycles, with expression of some genes during the light, even though most genes are more highly expressed in the dark (Colon-Lopez and Sherman, 1998;Stoeckel et al, 2008;Toepel et al, 2008). The Fe-Mo structural protein nifK, which is encoded for by the nifHDK polycistronic mRNA (Chen et al, 1998), had almost as many transcripts represented as nifH, which is the gene commonly used to examine diazotroph abundance and nitrogenase expression in environmental samples (Church et al, 2005;Short and Zehr, 2007;Zehr et al, 2007b).…”
Section: Resultsmentioning
confidence: 99%